Analisis Sistem Manajemen dalam Pemeliharaan Sarana dan Prasarana di Rumah Sakit Umum Daerah Teluk Kuantan Tahun 2016 - Candra, Leon; Widodo, M. Dedi; Tonis, Marian (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Installation Maintenance Infrastructure Hospital is an organization of a technical nature and coordinating the implementation of improving existing facilities and equipment in hospitals. This research is descriptive qualitative method, by the number of informants 5 persons, the Hospital Director, Head Installation Maintenance of facilities and infrastructure Hospital, Head of Civil Service, Technician two people. This research was conducted by conducting in-depth interviews and observation. Data processing is done by triangulation, triangulation methods and triangulation of data, the data obtained will be analyzed and explained in accordance with existing theories. The result research shows that the organization has been running well but not maximum, because of human resources for the Installation Maintenance Facility Hospital is still inadequate and placement of human resources have not been in their respective fields, Installation Maintenance costs for Hospital Infrastructure is not maximized, and to methods already well underway. It is expected to be in management, human resources in order to be empowered again, costs and methods reevalu ated, so that the overall maintenance system can work better. Keyword : The management system, the maintenance of infrastrukture, hospital